Improving agricultural knowledge management: The AgTrials experience [version 1; referees: 2 approved] - Hyman, Glenn G.; Espinosa, Herlin; Camargo, Paola; Abreu, David; Devare, Medha; Arnaud, Elizabeth; Porter, C.H.; Mwanzia, Leroy; Sonder, Kai; Sibiry Traoré, Pierre C. (F1000 Research Ltd, 2017)
Background: Opportunities to use data and information to address challenges in international agricultural research and development are expanding rapidly. The use of agricultural trial and evaluation data has enormous potential to improve crops and management practices. However, for a number of reasons, this potential has yet to be realized. This paper reports on the experience of the AgTrials initiative, an effort to build an online database of agricultural trials applying principles of interoperability and open access. Methods: Our analysis evaluates what worked and what did not work in the development of the AgTrials information resource. We analyzed data on our users and their interaction with the platform. We also surveyed our users to gauge their perceptions of the utility of the online database. Results: The study revealed barriers to participation and impediments to interaction, opportunities for improving agricultural knowledge management and a large potential for the use of trial and evaluation data. Conclusions: Technical and logistical mechanisms for developing interoperable online databases are well advanced. More effort will be needed to advance organizational and institutional work for these types of databases to realize their potential.